2001
DOI: 10.1053/jvet.2001.25875
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐articular absorbable suture stabilization of coxofemoral luxation in dogs

Abstract: Absorbable sutures avoid the possible complications related to the use of nonabsorbable material and seem to be sufficient to maintain articular stability during the capsular healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 19 publications
0
52
0
16
Order By: Relevance
“…Some studies on hip luxation and subsequent joint capsule and ligament healing showed that fibrous reaction of the joint capsule and round ligament healing occurred at 14 th day [39] . Also, using of Ehmer sling or other temporary stabilization materials for 2 weeks has been shown to be effective enough in ensuring the long term stability of the joint [6,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on hip luxation and subsequent joint capsule and ligament healing showed that fibrous reaction of the joint capsule and round ligament healing occurred at 14 th day [39] . Also, using of Ehmer sling or other temporary stabilization materials for 2 weeks has been shown to be effective enough in ensuring the long term stability of the joint [6,13] .…”
Section: Discussionmentioning
confidence: 99%
“…CFL'larda cerrahi stabilizasyon, kapalı metotla başarı sağlanamadığına ya da eklemin açık olarak incelenmesinin gerekli olduğu durumlarda endikedir (3,13,19). CFL'ların cerrahi sağaltımında bir çok teknik tanımlanmakla beraber hiç birisi tek başına ideal değildir (17,19). Bu çalışmada tüm olguların öncelikle kapalı redüksiyon ile CFL sağaltım-ları denenmiş ancak başarısız olunması nedeniyle tamamında açık redüksiyon ve stabilizasyona gidilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…CFL, küçük hayvan hekimliğinde önemli bir yeri olan ve tüm luksasyon olguları içinde en büyük paya (yaklaşık %64-90) sahip olan luksasyon tipidir (4,5,7,9,12,(16)(17)(18)(19)(20)(21)25) ve omuz ve dirsek eklemi luksasyonlarından iki kat daha fazla sıklıkta izlenir (7). CFL'nun en yaygın nedeni trafik kazalarıdır (%59-85) (5,10,20,24), bunu yüksekten düşme ve nedeni bilinmeyen travmalar takip eder (24).…”
Section: Introductionunclassified
See 2 more Smart Citations